Genomic Changes and Genetic Divergence of Vibrio alginolyticus Under Phage Infection Stress Revealed by Whole-Genome Sequencing and Resequencing - Zhou, Wenjie; Li, Yingying; Li, Zhuobo; Ma, Bo; Jiang, Xiao; Hu, Chaoqun; Ai, Yongxing; Luo, Peng (Frontiers in Microbiology, 2021)
Bacteriophages (phages) and their bacterial hosts were the most abundant and genetically highly diverse organisms on the earth. In this study, a series of phage-resistant mutant (PRM) strains derived from Vibrio alginolyticus were isolated and Infrequent-restriction-site PCR (IRS-PCR) was used to investigate the genetic diversity of the PRM strains. Phenotypic variations of eight PRM strains were analyzed using profiles of utilizing carbon sources and chemical sensitivity. Genetic variations of eight PRM strains and coevolved V. alginolyticus populations with phages were analyzed by whole-genome sequencing and resequencing, respectively. The results indicated that eight genetically discrepant PRM stains exhibited abundant and abundant phenotypic variations. Eight PRM strains and coevolved V. alginolyticus populations (VE1, VE2, and VE3) contained numerous single nucleotide variations (SNVs) and insertions/indels (InDels)and exhibited obvious genetic divergence. Most of the SNVs and InDels in coding genes were related to the synthesis of flagellar, extracellular polysaccharide (EPS), which often served as the receptors of phage invasion. The PRM strains and the coevolved cell populations also contained frequent mutations in tRNA and rRNA genes. Two out of three coevolved populations (VE1 and VE2) contained a large mutation segment severely deconstructing gene nrdA, which was predictably responsible for the booming of mutation rate in the genome. In summary, numerous mutations and genetic divergence were detected in the genomes of V. alginolyticus PRM strains and in coevolved cell populations of V. alginolyticus under phage infection stress. The phage infection stress may provide an important force driving genomic evolution of V. alginolyticus.